Osteoarthritis in Iceland. An archaeological study - Hildur Gestsdóttir 1972- (2014)
Osteoarthritis has been intensively studied within the field of palaeopathology. For decades there was assumed to be a direct link between activity and the development of osteoarthritis, and this was reflected in the work which was carried out, with often very specific interpretations of occupation and activity on the basis of the diagnosis of osteoarthritis. By the 1990s it began to be more accepted within the field that the aetiology of osteoarthritis is far too multifactorial to allow for such simplistic conclusions to be drawn. This has resulted in a great reduction in the interest in the study of osteoarthritis within palaeopathology in the past few decades, as the condition appears to have somewhat lost its place within the archaeological discussion. Within the medical community, the focus has shifted in the past three decades to the genetic aetiopathogenesis of osteoarthritis. There has been a great deal of work in this field in Iceland, where the genetic link to hip, hand, and to a lesser extent knee osteoarthritis has been demonstrated, with the identification of several osteoarthritis families within the population. The main aim of this thesis is to reclaim the study of osteoarthritis within palaeo¬pathology using the analysis of the condition within five Icelandic skeletal populations, kuml, Skeljastaðir, Hofstaðir, Haffjarðarey and Reykjavík, which span the occupation of Iceland, from the earliest settlement in the late 9th century to the 19th century. The approach to this is twofold. First of all, to avoid focusing on just one aetiological aspect of osteoarthritis, but rather to embrace its multifactorial nature, and consider multiple aetiological agents of the condition. These are in particular genetics, activity, anatomy, age and sex. The aim is then to place the results of the analysis within the social and physical environments of the populations under study, and so attempt to find osteoarthritis a place within the osteoarchaeological discussion again. Secondly, the aim is to consider a more ...